Uranium politics of gatekeeping : revisiting the British government's policy vis-à-vis South Africa, 1945-1951 (Historia, 2021)
The year 1945 signalled the use of nuclear weapons technology that ensured both an end of one war and the beginning of another - two global but dissimilar wars: the Second World War and the Cold War respectively. These marked the beginning of an increased quest for uranium residue for peaceful and military purposes by the principal state actors in the wars. It is suggested that the US relied on British Commonwealth connection to obtain uranium from South Africa between 1947 and 1951. However, after consulting multi-archival sources in Britain, Canada and South Africa, I argue that this earlier assertion is incorrect. It was only partially correct while Smuts was prime minister of the Union of South Africa and was certainly not true after 1948.  Die jaar 1945 het die gebruik van kernwapentegnologie ingelui, wat sowel 'n einde as 'n begin verseker het van twee wêreldwye, maar ongelyksoortige oorloë: die Tweede Wêreldoorlog en die Koue Oorlog onderskeidelik. Dit baken die begin af van 'n verskerpte soeke na uraanresidu vir vreedsame en militêre doeleindes deur die hoofrolspelende state in dié oorloë. Daar is gesuggereer dat die Verenigde State staatgemaak het op Britse Gemenebesbande om tussen 1947 en 1951 uraan vanaf Suid-Afrika te verkry. Na raadpleging van veelvoudige argiefbronne in Brittanje, Kanada en Suid-Afrika, voer ek aan dat die vroeëre bewering foutief is. Dit was slegs gedeeltelik waar terwyl Smuts eerste minister van die Unie van Suid-Afrika was en was beslis nie waar na 1948 nie.
Keywords: Atoomverhoudings; Natural resources; Uraan; Nasionale Party regering; Atomic relations; Britain; Second World War; Tweede Wereldoorlog; Jan Smuts regering; Commonwealth; Verenigde State; United States; Uranium; Gemenebes; National Party government; Unie van Suid-Afrika; Union of South Africa